Cerebrospinal Fluid Biomarkers for Diagnosis of Alzheimer’s Disease (Bangladesh Journal of Neuroscience, 2015)
Alzheimer’s disease is the most common cause of dementia among elderly people. The major pathological hallmarks of AD are the loss of neurons, occurrence of extracellular senile plaques as well as intracellular neurofibrillary tangles (NFT). Biochemical changes in the brain are reflected in the cerebrospinal fluid (CSF), and intense research efforts have been made to develop biomarkers for the central pathogenic processes in AD that can be used as diagnostic tools. Biomarkers are essential part of disease management as they are essential for diagnosis, monitoring the disease progression, detecting early onset of the disease, monitoring the effect of therapeutic intervention, and also avoiding false diagnosis of the disease. Unfortunately, none of the biomarkers presently available are able to accomplish the disease diagnosis single-handedly. Three CSF biomarkers, Aâ42, Total-tau (t-tau), and phosphorylated-tau (p-tau), have been found to have the highest diagnostic potential.Bangladesh Journal of Neuroscience 2015; Vol. 31 (1): 34-41